Decision Support System Using the SMART Method in Determining the Status of Contract Employees from Permanent Employees - Nitami, Dian; Rianti, Eva; Pratiwi, Mutiana (Journal of Computer Scine and Information Technology, 2024)
Employee performance assessment is a way to determine the abilities of each employee. The assessment is carried out to obtain materials for developing the company's human resources. The process of appointing contract employees to permanent positions is still not effective, this results in doubt in decision making which allows errors to occur. In this research, a system for decision making will be built, where this research uses the Multi Attribute Rating Technique (SMART) method. The SMART method is a multi-criteria decision making technique that compares one criterion with another. The data used in this research uses 3 factors and 12 employee data to be selected. For assessment using the SMART method based on criteria and weights, a score above 80 is declared a pass to become a permanent employee. Research using the Simple SMART method can help the Ibnu Sina Islamic Hospital in West Pasaman in managing the data or criteria used in determining the status of contract employees, so that they can determine employees who are in accordance with the quality and quantity of human resources needed and as a basis for making decisions. become a permanent employee.